Policy Concept for Repatriation of Problematic Indonesian Migrant Workers (TKIB) - Daniel Daniel; Suparno Suparno (Publikasiku, 2023)
The policy for the repatriation of Indonesian workers in certain situations is regulated by Presidential Regulation of the Republic of Indonesia Number 45 of 2013 concerning the Coordination of the Repatriation of Indonesian Migrant Workers to overcome them, but in its implementation, there are still obstacles that occur, especially in the funding sector. Nevertheless, the Government must continue to ensure the presence of TKI starting from the pre-placement stage, during placement, and after placement. This conception of employment is used as a reference for reviewing the existing legal instruments, whether they already cover these fields or not.